The Creation of Geotechnical Seismic Isolation from Materials with Damping Properties for the Protection of Architectural Monuments - Yerik T. Bessimbayev; Sayat E. Niyetbay; Talal Awwad; Erzhan I. Kuldeyev; Saken S. Uderbayev; Zhanar O. Zhumadilova; Zauresh M. Zhambakina (Buildings, 2024)
This paper presents the results of a study on the relevance of seismic isolation systems for protecting architectural monuments from seismic and vibration impacts. This work aims to develop a method for protecting architectural monuments from seismic and vibration effects by installing geotechnical seismic isolation systems made of various geomaterials, such as a silicate soil mixture (SSM), a cement–soil mixture (CSM), a bitumen–soil mixture (BSM), and a rubber–soil mixture (RSM). The novelty of the work lies in the results of studying the wave processes in different models of geomaterials to assess their effectiveness in a seismic isolation system in the form of damping barrier screens to ensure the seismic resistance of architectural monuments. By comparing the amplitude–frequency characteristics of various geomaterials, it was found that the rubber–soil mixture (RSM), the cement–soil mixture (CSM), and the bitumen–soil mixture (BSM) have the most effective damping properties. A proposed method for protecting architectural monuments with geotechnical seismic isolation in the form of vertical screen barriers and technology for their installation ensures the integrity and safety of architectural monuments at all stages of construction and operation.